2021
DOI: 10.1093/rheumatology/keab562
|View full text |Cite
|
Sign up to set email alerts
|

Socio-demographic determinants in the evolution of pain in inflammatory rheumatic diseases: results from ESPOIR and DESIR cohorts

Abstract: Objective To determine whether sociodemographic factors are associated with heterogeneity in pain evolution in inflammatory rheumatic diseases (IRDs) after accounting for disease-specific characteristics in a system with universal health care. Methods This analysis included the data from two prospective observational cohorts of early IRDs (ESPOIR for early rheumatoid arthritis (RA) and DESIR for early spondyloarthritis (SpA))… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“… 39 However, substantial evidence has now significantly broadened this perspective, highlighting the equal importance of biological, psychological and social determinants in understanding pain. 21 , 40 , 41 This holistic view is reflected in the biopsychosocial model of chronic pain. 22 As well as the identification of specific pain descriptors, recognising the need to assess the interplay between biological, psychological and social factors in each individual's experience of pain has important implications for stratified pain treatment, setting the path for more effective pain management.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 39 However, substantial evidence has now significantly broadened this perspective, highlighting the equal importance of biological, psychological and social determinants in understanding pain. 21 , 40 , 41 This holistic view is reflected in the biopsychosocial model of chronic pain. 22 As well as the identification of specific pain descriptors, recognising the need to assess the interplay between biological, psychological and social factors in each individual's experience of pain has important implications for stratified pain treatment, setting the path for more effective pain management.…”
Section: Discussionmentioning
confidence: 99%
“…Historically, pain was understood to correlate directly with the underlying biological pathology, and psychological factors were considered only in the absence of identifiable physical causes 39 . However, substantial evidence has now significantly broadened this perspective, highlighting the equal importance of biological, psychological and social determinants in understanding pain 21,40,41 . This holistic view is reflected in the biopsychosocial model of chronic pain 22 .…”
Section: Discussionmentioning
confidence: 99%
“…Our results will ultimately inform strategies to strengthen patient self-management, reduce anxiety surrounding health conditions, and reduce morbidity and mortality from adverse health outcomes. In addition, early identification of at-risk populations and implementation of multidisciplinary strategies may reduce patient-reported health outcome disparities [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, sociodemographic factors in patients with AIRDs have been linked to higher pain levels, deteriorating mental health, and overall poorer quality of life [ 2 , 8 ]. These findings underscore the importance of considering the broader context of a patient's life and socioeconomic situation when providing care and treatment for AIRDs.…”
Section: Introductionmentioning
confidence: 99%
“…These findings are similar to those from a large French observational study, which highlighted the temporal implications of pain heterogeneity and sociodemographic characteristics throughout the disease course. 44 Over the last two decades, the comorbidity burden at the time of RA diagnosis has risen, implying the need for early identification and better treatment tailoring for these at-risk individuals. 45 Additionally, our study findings have demonstrated high proportions of self-reported depression in those with poorer pain-related health status.…”
Section: Discussionmentioning
confidence: 99%